Detection of two power-law tails in the probability distribution functions of massive GMCs - Schneider, N.; Bontemps, S.; Girichidis, P.; Rayner, T.; Motte, F.; André, Ph; Russeil, D.; Abergel, A.; Anderson, L.; Arzoumanian, D.; Benedettini, M.; Csengeri, T.; et al. (Monthly notices of the Royal Astronomical Society, 2015)
We report the novel detection of complex high column density tails in the probability distribution functions (PDFs) for three high-mass star-forming regions (CepOB3, MonR2, NGC 6334), obtained from dust emission observed with Herschel. The low column density range can be fitted with a lognormal distribution. A first power-law tail starts above an extinction (A V) of ∼6–14. It has a slope of α = 1.3–2 for the ρ ∝ r −α profile for an equivalent density distribution (spherical or cylindrical geometry), and is thus consistent with free-fall gravitational collapse. Above A V ∼40, 60, and 140, we detect an excess that can be fitted by a flatter power-law tail with α > 2. It correlates with the central regions of the cloud (ridges/hubs) of size ∼1 pc and densities above 104 cm−3. This excess may be caused by physical processes that slow down collapse and reduce the flow of mass towards higher densities. Possible are: (1) rotation, which introduces an angular momentum barrier, (2) increasing optical depth and weaker cooling, (3) magnetic fields, (4) geometrical effects, and (5) protostellar feedback. The excess/second power-law tail is closely linked to high-mass star-formation though it does not imply a universal column density threshold for the formation of (high-mass) stars.